2021
DOI: 10.1017/dmp.2021.261
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of COVID-19 among Illiterate Population in Pakistan: A Cross-Sectional Analysis

Abstract: Background: COVIID-19 outbreak has been accompanied by a massive infodemic. However, many vulnerable individuals such as illiterate or low-literate, older adults, and rural populations have limited access to health information. In this context, these individuals are more likely to have poor knowledge, attitudes, and preventive practices related to COVID-19. The current study was aimed to investigate COVID-19’s awareness of the illiterate population of Pakistanis. Methods: A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Similarly, we´ve found that the most vulnerable populations were first reached by the COVID-19 pandemic in Brazil, including indigenous and elderly and those living in areas where environmental conditions are worsened. Similar findings have been documented in Brazil and elsewhere, confirming that worsened social and environmental conditions could greatly contribute to the speed of the disease spread [ 13 , 14 , 16 , 31 34 ]. However, it is important to consider the unique context of some regions, such as small southern cities with meatpacking plants.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, we´ve found that the most vulnerable populations were first reached by the COVID-19 pandemic in Brazil, including indigenous and elderly and those living in areas where environmental conditions are worsened. Similar findings have been documented in Brazil and elsewhere, confirming that worsened social and environmental conditions could greatly contribute to the speed of the disease spread [ 13 , 14 , 16 , 31 34 ]. However, it is important to consider the unique context of some regions, such as small southern cities with meatpacking plants.…”
Section: Discussionsupporting
confidence: 83%
“…Psychoeducation or cognitive behavior therapies have been well = recommended during such circumstances [ 51 ]. The implementation of community-based strategies, telehealth services and awareness programs for self-relaxation and self-care can provide promising psychological support to this vulnerable population [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the strong family network and cohesion may lead to physical meetings and gatherings to care for the loved ones and must be weighed against the need to reduce the likelihood of infection transmission by adhering to the social restriction regulations. COVID-19 knowledge, attitude, and preventive practices have been shown to be low among the majority of the Pakistani population [ 38 ].…”
Section: Discussionmentioning
confidence: 99%